Advanced mechanical characterization of NHL mortars and cohesive simulation of their failure behavior. (30th October 2017) - Garijo, Lucía; Zhang, Xiaoxin; Ruiz, Gonzalo; Ortega, José J.; Yu, Rena C.
Highlights: Full mechanical characterization of NHL mortars including the fracture energy. Great influence of water/lime ratios on the mechanical properties. Different results of compressive strength in prisms and cylinders. Numerical simulation of the cohesive behavior of NHL mortars. Numerical demonstration of shape and size effects in the compressive tests. Abstract: An advanced mechanical characterization of two natural hydraulic lime (NHL) mortars, with water/lime ratios of 0.8 and 1.1, is reported, including direct measurement of the compressive strength on two types of specimens, prisms and cylinders, the flexural strength, the tensile strength, the Young's modulus and the fracture energy. The results are significantly lower for the higher water/lime ratio. Besides, the compressive strength depends very much on the type of specimen used. A cohesive simulation is performed to prove that such variations in the compressive strength are due to the effect of the shape and size of the specimen.